A Practical Method for Camera Calibration in Stereo Vision Mobile Robot Navigation - Hamzah, Rostam Affendi; Abd Ghani, SHAMSUL FAKHAR; Kadmin, AHMAD FAUZAN; A Aziz, Khairul Azha (2012)
This paper presents a method of camera calibration of stereo pair for stereo vision application. The method is using Jean-Yves Bouguet tool which produces the intrinsic and extrinsic parameters of stereo pair. The data of calibration will be used in image rectification between two images. Then the rectified image will go through the block matching process. The block matching technique is briefly described with the performance of its output. The disparity mapping is generated by the algorithm with the reference to the left image coordinate. The algorithm uses Sum of Absolute Differences (SAD) which is developed using Matlab software.